Casein glycomacropeptide pH-driven self-assembly and gelation upon heating - Martinez, María Julia (2011)
Casein glycomacropeptide (CMP) found in cheese whey is a C-terminal hydrophilic glycopeptide released from κ-casein by the action of chymosin during cheese making. In a previous work a self-assembly model for CMP at room temperature was proposed, involving a first step of hydrophobic assembly followed by a second step of electrostatic interactions which occurs below pH 4.5. The objective of the present work was to study, by dynamic light scattering (DLS), the effect of heating (35-85 °C) on the pH-driven CMP self-assembly and its impact on the dynamics of CMP gelation. The concentration of CMP was 3%. w/w for DLS and 12%. w/w for rheological measurements. The solutions at pH 4.5 and 6.5 did not show any change in the particle size distributions upon heating. In contrast the solutions at pH lower than 4.5 that showed electrostatic self-assembly at room temperature were affected by heating. The mean diameter of assembled CMP increased by decreasing pH. For all solutions with pH lower than 4.5, the particle size did not change on cooling, suggesting that the assembled CMP forms formed during heating were stable. The gel point determined as G'-G″ crossover, occurred in all systems at 70 °C, but at different times. The rate of self-assembly determined by DLS as well as the rate of gelation increased with increasing temperature and decreasing pH from 4 to 2. Increasing temperature and decreasing pH, the first step of CMP self-assembly by hydrophobic interactions is speed out. All the self-assembled structures and the gels formed at different temperatures were pH-reversible but did not revert to the initial size (monomer) but to associated forms that correspond mainly to CMP dimers.